Third contibution to the sawflies (Hymenoptera: Symphyta) of Kintrishi Nature Reserve (Georgia, Sakartvelo) (Part III) - Japoshvili, G.; Haris, A. (The Journal of Nature Studies - Annals of Agrarian Science, 2023)
2 482 specimen belonging to 89 sawflies species are listed from the 1 264 m altitude of Kintrishi National Park. Characteristic species are: Onycholyda trigaria (Konow, 1897), Birka catellata (Konow, 1900), Strongylogaster caucasica Schaposchnikov, 1885, Eutomostethus ephippium ssp. vopiscus (Konow, 1899), Macrophya hamata ssp. caucasicola Muche, 1969, Sciapteryx byzantina Benson, 1968, Tenthredo albopicta Puls, 1870, Tenthredo purpurea Puls, 1870, Tenthredo radoszkowskii (André, 1881), Tenthredo shaposhnikovi (Dovnar-Zapolskij, 1930), Tenthredo talyshensis Zhelochovtsev, 1988 and Tenthredopsis viridis Zhelochovtsev, 1941. Zoogeo graphic distributions of sawflies were analyzed and discussed. The known number of sawflies increased up to 142 in Kintrishi National Park. Twenty species are new records for the fauna of Georgia. Six genera Periclista Konow, 1886, Amauronematus Konow, 1890, Eupontania Zinovjev, 1985, Euura Newman, 1837, Phyllocolpa Benson, 1960 and Pontania Costa, 1852.